Changes in muscle activity pattern in lower limb extremity during pedalling by saddle height - Choi, J. S.; Kang, D. W.; Bae, J. H.; Shin, Y. H.; Lee, J. H.; Tack, G. R. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
As a preliminary study for a preferential saddle height for cyclist, muscle activity pattern in lower limb extremity between preferred and higher saddle height during pedalling was compared. Seven cyclists performed 3 min sub-maximal pedalling under two different saddle heights. Range of motion (ROM) of muscle length, onset-timing of muscle activity, and amount of muscle activity in biceps femoris (BF), vastus lateralis (VL), gastrocnemius (GM), and tibialis anterior muscles (TA) were used to compare changes in muscle activity pattern due to saddle height. Results showed that there was a significant difference in ROM of VL and that of TA (p<.05), and there was a significant difference in onset-timing of BF and that of GM (p<.05). In all muscle, there was no difference in the amount of muscle activity. Further study is necessary to study the effect of various conditions (saddle heights as well as loads and cadences) on muscle activity pattern.